Comparing apples with oranges: revisiting the gender wage gap in an international perspective - Plasman, Robert; Sissoko, Salimata (Bonn, 2004)
"Using a rich and comparable micro-data set, we analyse international differences in gender pay gaps in the private sector for a sample of five European economies: Belgium, Denmark, Ireland, Italy and Spain. Using different methods, we examine how wage structure, differences in the distribution of measured characteristics, occupational and industrial segregation contribute to explain the pattern of international differences. Furthermore, we take into account indirect discrimination influencing female occupational and industrial distributions. We find significant impacts of those latter factors on gender differentials. However, the magnitude of their effects varies across countries."